A descriptive analysis of single-word Ilongo Hiligaynon adverbs - Navales, Estrella Q. 1924- (1966)
This paper provides a description of the following features of adverbs in Ilonggo Hiligaynon: classes of adverbs, adverb comparison and intensification, and word order.